2017
DOI: 10.21037/atm.2017.08.21
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of different suture closure methods: barbed versus traditional interrupted sutures

Abstract: Healthcare systems are receiving increasing pressures from payers, such as the Centers for Medicare and Medicaid (CMS), to reduce the costs associated with procedures, and with the implementation of the Affordable Care Act, high costs are addressed through pay-for-performance programs. Thus, multiple areas of total knee arthroplasty (TKA) surgery are under scrutiny, including surgical times, material costs, and the costs of associated complications and readmissions. Suture type has been determined to be a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Within the setting of orthopaedic surgery it has been demonstrated that usage of barbed suture materials for wound closure lead to an overall cost saving, largely as a result of reduced operative times compared with interrupted sutures. 29 Two of the studies included within the current analysis were able to demonstrate reduced material costs when using a barbed suture material in a continuous method compared with interrupted stitches using standard suture materials. 15,17 One study also hypothesised that the potential reduction in operating theatre time would reduce the overall costs of each procedure by approximately US $200, 22 which would easily offset the additional costs of the barbed suture material.…”
Section: Discussionmentioning
confidence: 85%
“…Within the setting of orthopaedic surgery it has been demonstrated that usage of barbed suture materials for wound closure lead to an overall cost saving, largely as a result of reduced operative times compared with interrupted sutures. 29 Two of the studies included within the current analysis were able to demonstrate reduced material costs when using a barbed suture material in a continuous method compared with interrupted stitches using standard suture materials. 15,17 One study also hypothesised that the potential reduction in operating theatre time would reduce the overall costs of each procedure by approximately US $200, 22 which would easily offset the additional costs of the barbed suture material.…”
Section: Discussionmentioning
confidence: 85%
“…12,13 As the United States healthcare system shifts towards a bundled-payment based reimbursement model, increasing attention and scrutiny have been direct towards potential methods to improve quality of care and reduce costs. 14 Barbed sutures may reduce operative time, costs, and complications associated with THA 1,3,15 Prior studies have evaluated the use of barbed sutures for superficial closure after THA. 7,8 These studies generally support the use of barbed sutures in superficial closure, but they have been limited by non-random design and their applicability to closure of the arthrotomy is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Closure with barbed sutures theoretically produces water-tight wounds and also provides other benefits such as reduced closure time, lower rates of infection, and lower total hospital costs. 3 A recent systematic review of closure modalities concluded that barbed sutures may in fact significantly reduce closure time; however, this report noted that the inconsistent designs and methodological features of prior studies limited the strength of conclusions regarding these sutures. 1…”
Section: Introductionmentioning
confidence: 91%
“…In terms of costs, based on head‐to‐head comparison from one trial included in our systematic review, barbed sutures were found to be costlier than the conventional sutures. In terms of the cost of the suture itself, it was found that the cost per stitch for monofilament absorbable sutures ranged between US$ 1.75 and US$ 1.83, and the cost per stitch for barbed sutures was US$ 19.96 30 . However, when determining cost‐effectiveness of interventions in obstetrics, consideration should be given to long‐ and short‐term consequences to mother and baby, in addition to the implications for healthcare systems 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the cost of the suture itself, it was found that the cost per stitch for monofilament absorbable sutures ranged between US$ 1.75 and US$ 1.83, and the cost per stitch for barbed sutures was US$ 19.96. 30 However, when determining cost-effectiveness of interventions in obstetrics, consideration should be given to long-and short-term consequences to mother and baby, in addition to the implications for healthcare systems. 31,32 Currently, the small reduction in the operative time and estimated blood loss in cesarean deliveries may not justify the use of barbed sutures routinely.…”
Section: Countrymentioning
confidence: 99%